Pemanfaatan Media Video Pembelajaran Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Matematika Materi Bangun Ruang: Utilization of Learning Video Media to Improve Student Learning Outcomes in Mathematics Subjects in Building Materials - Teneng Teneng (Neraca: Jurnal Pendidikan Ekonomi, 2023)
The aims of the research were: 1) to explain techniques or how to use learning video media to improve student learning outcomes in mathematics subject matter for building space materials in class VI of SDN-2 Samba Danum. 2) Proves that Learning Video Media Can Improve Student Learning Outcomes in Subjects. The results of the research show that learning video media can improve student learning outcomes in mathematics in class VI-B SDN-2 Samba. 1410 with a class average score of 67.14 and in Cycle 2 the total student score was 1590 with a class average of 75.24. It is proven that there is an increase in the class average value of 8.10 value points. Cycle 1 there were 8 or 38.09% of students, and students who completed 13 students or 61.90% who scored Mathematics and students who completed 3 people or 60% of the total number of students, namely 21 students and in cycle 2 it was proven the value of the Mathematics subject was 20 students who completed or 95.24% of students from the total number of students, namely 21 students.